Biodegradation Of Diesel By A Locally Isolated Acinetobacter Sp. - Dahalan, Farrah Aini (2007)
Local bacteria isolated from oil-contaminated soils from various locations in Malaysia were screened for their ability to degrade commercial diesel fuel. Enrichment culture from soil samples yielded several isolates capable of degrading diesel. Of these, Isolate 1 was selected for further studies based on its best growth performance compared to the other isolates. Biodegradation studies were conducted using head-space solid-phase microextraction (HS-SPME: 110°C, 10 min, 7 μm PDMS fiber and 25% NaCl) coupled to gas chromatography equipped with flame ionization detector (GC-FID). The isolate was identified as Acinetobacter sp. (1470 bp) (98% sequence homology) using 16s rRNA molecular phylogenetic analysis. Isolate 1 exhibited optimum growth at 37°C in media containing 4% (v/v) diesel, and is able to degrade 51.7% of diesel in 6 days. Isolate 1 was grown on various nitrogen sources such as NH4Cl, NH4SO4, NaNO3, and KNO3. The best nitrogen source is potassium nitrate (KNO3) at 0.9% (v/v). Its optimized optimum pH for growth is pH 7.5. Five different diesel-degrading enzymes were detected: alkane-oxidizing enzyme (0.2.8 μmol min-1 ml-1), alcohol dehydrogenase (9.0956 μmol min-1 ml-1), aldehyde dehydrogenase (4.234 μmol min-1 ml-1), pyridine nucleotide-independent dehydrogenase (4.229 μmol min-1 ml-1) and aldehyde reductase (8.126 μmol min-1 ml-1)